CYT003, a TLR9 agonist, in persistent allergic asthma – a randomized placebo‐controlled Phase 2b study. Issue 9 (22nd June 2015) - Casale, T. B.; Cole, J.; Beck, E.; Vogelmeier, C. F.; Willers, J.; Lassen, C.; Hammann‐Haenni, A.; Trokan, L.; Saudan, P.; Wechsler, M. E.
Abstract Background New treatment options are required for patients with asthma not sufficiently controlled with inhaled therapies. In a Phase 2a trial, CYT003, a Toll‐like receptor‐9 agonist immunomodulator, improved asthma control during inhaled glucocorticosteroid reduction in patients with allergic asthma. This double‐blind Phase 2b study assessed the efficacy and safety of CYT003 in patients with persistent moderate‐to‐severe allergic asthma not sufficiently controlled on standard inhaled glucocorticosteroid therapy with/without long‐acting beta‐agonists (LABAs). Methods Overall, 365 patients received seven doses of subcutaneous CYT003 (0.3, 1, or 2 mg) or placebo as add‐on therapy to conventional controller medication. Change from baseline in Asthma Control Questionnaire (ACQ) score was the primary outcome; secondary outcomes included change in forced expiratory volume, Mini Asthma Quality of Life Questionnaire, and safety. Results All groups, including placebo, showed a clinically important improvement in ACQ score; however, there was no significant difference between the CYT003 and placebo groups at week 12 (least‐squares mean difference 0.3 mg: −0.027 [95% confidence interval −0.259 to 0.204]; 1 mg: 0.097 [−0.131 to 0.325]; 2 mg: 0.081 [−0.148 to 0.315]). No significant differences were seen in secondary outcomes. CYT003 was well tolerated; the most common treatment‐emergent adverse events were injection site reactions. Due to lack of efficacy, the study was prematurely terminated at the end of the treatment phase with no further follow‐up. Conclusions Toll‐like receptor‐9 agonism with CYT003 showed no additional benefit in patients with insufficiently controlled moderate‐to‐severe allergic asthma receiving standard inhaled glucocorticosteroid therapy with or without LABAs.